Preparation and Characterization of Lithium-Based Solid State Battery Materials - Idrees, Muhammad Amin (2000)
Three different cathodes such as LiMn204, LiCo02 and Li2NigOlO were synthesized by the sol-gel technique The said materials at low temperature were achieved through the low temperature technique The X-ray diffraction study of the compounds confirmed the formation of single-phase compound at higher calcination temperature At low temperatures the X-ray diffractogram of the samples showed the presence of low intensity diffraction lines with weak impurities indicating the existence of crystallinity but these were not indexed to any kind of impurities of LiMn20-+ LiCoOz and LizNisOlO The formation temperatures of the compounds were analyzed using DTA. The DTA studies showed clearly the lowest formation temperature and this formation temperature depends upon the gelating agent used 111 the present study The lowest formation temperatures recorded were 208°C for LiMn20-+, 201°C for LiCo02 and 214°C for LjzNisOlO The thermogravimetric analysis showed that the compounds were stable up to 800 °c The EDAX analysis was performed for the compounds to identify the purity of the compounds The EDAX spectrum showed that there was no impurity pI esent in the compounds It ascertained the formation of single-phase compounds by XRD Because of low atomic weight lithium could not be detected other than that the EDAX showed the presence of the respective atoms The particle size distribution of the compounds showed that the particles were distributed in large volume The particle diameter increased with the increase of calcination temperature Grinding reduced the large volume distribution and the particle diameter After grinding by mortar and pestle hand grinder, the particle size was reduced much and the distribution was narrowed down, thereby the surface area of the particle was increased The SEM analysis also confirmed the sub-micron size reduction and the distribution was narrowed down, thereby the surface area of the particle was increased The compounds were used as electrode materials for lithium ion batteries The battery analysis showed that the capacities of the LiMn20, LiCo02 and Li2NisOIO were 10 mAh , 24 mAh and 5 mAh respectively